Embodying Emotion: Ontological Metaphors in Frances Hodgson Burnett`s Novel: The Secret Garden - Siti Nurhaliza; Hanafi Wibowo (Journal of Applied Linguistics, 2025)
This research examined how to analyze metaphors in the novel The Secret Garden by Frances Hodgson Burnett. Using Lakoff and Johnson's conceptual metaphor theory, the study examined 50 metaphors to explain how nature-based imagery converts abstract emotional notions into real sensations. The findings showed that ontological metaphors, which account for 60% of the investigated data, successfully represent emotions like hope, despair, and joy. Structural and orientational metaphors help to depict personal growth and cognitive-emotional interaction. This study emphasized the instructional usefulness of metaphors in children's reading, indicating their ability to improve emotional literacy and cognitive understanding. By bridging the gap between natural imagery and abstract emotional states, The Secret Garden is an effective narrative tool for readers to develop emotional resilience and personal growth. Keywords : Metaphor; Novels; The Secret Garden